Utilization of waste fabric as a learning media to grow students' entrepreneurial soul - Reva Maria Valianti; Neta Dian Lestari; Muhammad Kristiawan; Sudarwan Danim; Rambat Nur Sasongko (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The problem of the study is a lack of information about waste management, as well as a lack of entrepreneurial spirit. The purpose of this research is to foster an entrepreneurial spirit and to foster the development of an entrepreneurial spirit. Respondents were FKIP Universitas PGRI Palembang students. The descriptive technique was utilized. The debate analysis approach may be used to integrate research analysis in the context of this subject on how to generate creative goods from patchwork trash. Documentation, questionnaires, and interviews are used to collect data. The results revealed that (a) utilizing patchwork waste is a form of concern for the surrounding environment; (b) providing learning media by utilizing patchwork waste is a learning designed to increase students' motivation and entrepreneurial spirit; and (c) good implementation from planning to processing to marketing and preserving has obstacles and challenges, specifically how students are consistent with the products made and increase creativity in processing. This study provides an alternative media on growing students’ entrepreneurship skill.